(untitled) (Marketing Journal, 2025)
Today, the growth of environmental risks, the negative impact of climate change, and the urgency of environmental protection have made the concept of green insurance one of the key global directions. Green insurance serves as a financial tool to manage environmental risks, natural disasters, climate change, and other environment -related threats, contributing to the principles of sustainable development. This scientific study analyzes the necessity, current state, and prospects of green insurance in the insu rance market of Uzbekistan. Although this area has not yet been fully developed in the country, international experience, the governmentʼs focus on ecological policy, and the modernization of the financial sector demonstrate strong potential for its introd uction. The study also considers existing challenges, legal and institutional barriers, the preparedness of market participants, demand for innovative insurance products, and strategies for their implementation. As a result, practical recommendations are developed for the effective application of green insurance in Uzbekistan.